Pengaruh Struktur Modal, Pertumbuhan laba terhadap kualitas laba dan ukuran perusahaan sebagai variabel moderasi - Jaenal Abidin; Lodang Prananta Widya Sasana; Amelia Amelia (Politeknik Ganesha Medan, 2022)
Earnings quality as a measuring tool to assess the quality of financial information. The high quality of financial information comes from the high quality of financial reports.The purpose of this study is to examine the effect of capital structure, earning growth on earnings quality and firm size as moderasi variabels. The independen variabels used in this study are capital structure and earning growth. While the dependent variabel in this study is earning quality, and the moderasi variabel in this study is firm size. The type of research used in this study is quantitative research. Sources of data used in this study is secondary data. The populations in this study is the banking subsector companies listed on the Indonesia stock exchange during the 2015-2019 period. Determination of the sample in this study using purposive sampling method and obtained as many as 10 campanies multiplied by a period of 5 year so that the sample in this study is 50. The analysis using E-Views version 9 software. The results of this study indicate that the capital structure partially has no effect on earning quality. Profit growth partially has a negative effect on earning quality. Firm size partially effects has a positive effect on earning quality. Firm size partially doesn’t moderate capital structure on earning quality. Firm size partially doesn’t moderate earning growth on earning quality. Capital structure, earning growth, firm size simultaneously effect earning quality.